Investigation on Water Borne Protozoan Parasites in Drinking Water of Quetta and Sohbat Pur Districts of Balochistan (Journal of Agriculture and Veterinary Science, 2024)
Current study was aimed to investigate the prevalence of water-borne protozoa in drinking water and stool samples from suspected intestinal effected patients in districts Quetta and Sohbat Pur, Balochistan. For this purpose, 200 water samples were collected from different water sources of the selected study areas. Collected samples were transported to the Sardar Bahadur Khan Woman University for further processing. Similarly, 200 human stool samples were also collected and transported to the Bolan Medical complex microbiology laboratory for further processing. Staining of stool samples was done by iodine and modified acid fast stain and examined under microscope. Culturing of positive stool samples weas carried out using lock egg media to culture Entamoeba histolytica. Overall, 15% protozoan prevalence was recorded from the water samples collected among the selected study areas where higher prevalence was observed in Sohbat Pur (20%) followed by Quetta (10%). Among water bodies higher prevalence was observed in canal system (40%). Protozoan distribution was recorded higher in May and August (17.5%) in water samples. Overall, 22% protozoan prevalence was recorded from the stool samples and higher prevalence was recorded in Sohbat Pur (27%) followed by Quetta (18%). Children from age group 11-20 years were found more susceptible as compared to adults. Based on month wise prevalence, higher prevalence was recorded in August (27.5%) and lowest in July (17.5%). Entamoeba histolytica was found more prevalent (17%) as compared to Giardia lamblia (5.5%). Statistical analysis shows there is no significant difference (P>0.05) among water and stool samples of Quetta and Sohabat Pur district of Balochistan. Further importance of the current study is discussed.